APLIKASI PENJUALAN PRODUK DAN PELAYANAN JASA GROOMING DI CV. HIKMA PETSHOP BERBASIS WEB - Dini Haro Pertiwi; Adelia Pratiwi; Maria Veronica (JIKI (Jurnal llmu Komputer & lnformatika), 2022)
CV Hikma Petshop is one of the pet shops in Palembang that provides cat food, cat accessories, cages, etc. Apart from selling various kinds of food and accessories, CV Hikma Petshop also offers grooming services, also known as a special pet salon for cats, such as grooming, bathing, and cutting nails. Based on the data that has been collected from interviews, it is known that in recapitulating transaction data only using the manual method, namely using a calculator, thus causing the administrator's work process to take quite a long time. The design of this information system uses a prototype development model. This model was chosen to be used to design a system based on user needs. The prototype development model has five stages, namely identifying user needs, making prototypes, testing prototypes, making repairs to prototypes if previous tests have not been received, then the final stage is developing a production version. This website-based system is created using the PHP and MySQL programming languages ​​for database storage. The result of this Final Project is in the form of a website application that aims to help the recapitulation process of sales transaction data, where in this system it can store sales data, product data, and grooming service data.